Liveability Dimensions And Attributes: Their Relative Importance In The Eyes Of Neighbourhood Residents - Leby, Jasmine Lau; Hashim, Ahmad Hariza (Penerbit Universiti Sains Malaysia, 2010)
It is important for a neighbourhood to provide a quality and good environment to ensure that inhabitants are able to live their lives in a satisfying way. There have been few attempts to investigate people‟s perceptions about the places they currently live, especially what makes their neighbourhoods a good or bad place to live. Thus, this study aims (1) to identify the attributes and the dimensions that residents consider in evaluating the liveability of their neighbourhood and (2) to assess the importance of these attributes and dimensions. A literature review found that four dimensions are used in most studies to understand the liveability issues: social, physical, functional and safe. Sixteen attributes are also identified to be indicators for the four dimensions. The study was conducted in one of the neighbourhoods in the Subang Jaya Municipal Council vicinity, and data were collected using mailed questionnaires. A total of 170 questionnaires were completed and returned, which represented a 57% response rate. Results revealed that residents are most concerned about safety, while social issues are deemed to be the least important factor. Thus, efforts to promote neighbourhood liveability should be focused on ensuring the overall safety of the community by incorporating a design that creates territoriality and allows more surveillance. Neighbourhoods should be maintained to avoid incivilities to reduce the fear of crime and crime itself.